Effect of virtual simulation supported museum‐based learning on primary school students' multidisciplinary knowledge acquisition, learning motivation, critical thinking, creativity, and problem‐solving skills in C‐STEAM courses - Lixia Luo; Wenyao Shen; Qi Ye; Zehui Zhan; Wenkai Lin (Future in Educational Research)
Abstract The purpose of this study was to investigate the effects of virtual simulation‐supported museum‐based learning (VSS‐MBL) versus a traditional classroom on students' multidisciplinary knowledge acquisition, learning motivation, critical thinking, creativity, and problem‐solving skills in C‐STEAM courses. We invited 112 primary school students to participate in a series of C‐STEAM lessons in both VSS‐MBL (58 students) and traditional classroom settings (54 students). Students were able to interact with exhibits during their museum visit using virtual simulation technology, such as watching shadow play using AR and applying VR to draw personalized face paintings. Repeated ANOVA results showed that VSS‐MBL had a more significant impact on learning motivation, critical thinking, creativity, and problem‐solving skills than students learning in a traditional classroom setting. However, the significant effect on multidisciplinary knowledge acquisition was not as significant as learning in a traditional classroom environment, and there was no significant change in engineering knowledge. This study further discusses the reasons for this and provides scientific guidance for primary schools wishing to integrate C‐STEAM education into their museums.